2015
DOI: 10.5897/jeif2014.0629
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the monthly crude oil price forecasting accuracy via bagging ensemble models

Abstract: The study investigates the accuracy of bagging ensemble models (i.e., bagged artificial neural networks (BANN) and bagged regression trees (BRT)) in monthly crude oil price forecasting. Two ensemble models are obtained by coupling bagging and two simple machine learning models (i.e., artificial neural networks (ANN) and classification and regression trees (CART)) and results are compared with those of the single ANN and CART models. Analytical results suggest that ANN based models (ANN & BANN) are superior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 35 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Hacer et al [15] tried to forecast the monthly crude oil price using the bagging ensemble models and found that classification and regression trees perform better than artificial neural network-based models. With the idea of bagging being introduced, they claimed to have gained better accuracy in both the models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hacer et al [15] tried to forecast the monthly crude oil price using the bagging ensemble models and found that classification and regression trees perform better than artificial neural network-based models. With the idea of bagging being introduced, they claimed to have gained better accuracy in both the models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While in 2015, Aydogmus and Ekinci mainly investigated bagging ensemble models such as bagged artificial neural networks (BANN) and bagged regression trees (BRT). It is concluded that the bagging ensemble method could optimize the forecast accuracy [10]. Those papers have suggested ensemble learning algorithms have the potential to work well enough in forecasting areas.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth category, because the ensemble model is the integrated prediction of multiple same-type models, it can solve the issues that caused by the single model. It mainly include Bagging [34,35], Boosting [36], AdaBoost [37], and XGBoost [38,39], etc. At present, the ensemble model is widely used in various domains.…”
Section: Introductionmentioning
confidence: 99%